2021
DOI: 10.1785/0220210135
|View full text |Cite
|
Sign up to set email alerts
|

Imaging the Ice Sheet and Uppermost Crustal Structures with a Dense Linear Seismic Array in the Larsemann Hills, Prydz Bay, East Antarctica

Abstract: Comprehensive geophysical surveys including magnetotelluric, seismic, and aerial gravity–magnetic surveys are essential for understanding the history of Antarctic tectonics. The ice sheet and uppermost structure derived from those geophysical methods are relatively low resolution. Although ice-penetrating radar can provide high-resolution reflectivity images of the ice sheet, it cannot provide constraints on subice physical properties, which are important for geological understanding of the Antarctic continent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 45 publications
1
6
0
Order By: Relevance
“…They are concentrated near the grounding line (Figure 13b). The optimal velocities are ∼1.7 km/s, consistent with the surface wave velocity within the glacier (Fu et al., 2023).…”
Section: Discussionsupporting
confidence: 70%
“…They are concentrated near the grounding line (Figure 13b). The optimal velocities are ∼1.7 km/s, consistent with the surface wave velocity within the glacier (Fu et al., 2023).…”
Section: Discussionsupporting
confidence: 70%
“…velocities previously published byFu et al (2022), shown in Figures2a-2c, respectively. The stacked CRF results, generated from four earthquakes with magnitudes greater than 5.8 (indicated by purple circles in FigureS1in Supporting Information S1), are presented in Figure2b.…”
mentioning
confidence: 54%
“…Seismic analysis of the Larsemann Hills seismic data yielded three seismic products: the average crustal Poisson's ratio (Zhu & Kanamori, 2000) beneath each seismic station, stacked Coherent Receiver Function (CRF) image, and shallow seismic velocities previously published by Fu et al. (2022), shown in Figures 2a–2c, respectively. The stacked CRF results, generated from four earthquakes with magnitudes greater than 5.8 (indicated by purple circles in Figure S1 in Supporting Information ), are presented in Figure 2b.…”
Section: Data and Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, shear waves enable better constraints on seismic anisotropy in ice sheets compared to P waves (Diez et al., 2016). Surface wave dispersion curve inversion has been widely used for imaging the shallow structures of the Antarctic (Diez et al., 2016; Fu et al., 2021; Picotti et al., 2015; Shen et al., 2018). The derived 1D velocity models are first‐order approximations of a heterogeneous Earth.…”
Section: Introductionmentioning
confidence: 99%